Strategies to promote the values of national belonging among Sudanese migrants - Al Tarifi, Muhied Abdullah (Journal of Humanities & Social Sciences, 2017)
This study aimed to explain the best strategies to reinforce the values of national affiliation among Sudanese expatriates. It also aims to recognize the statistical indicative differences in the responses provided by members of the sample group, which are attributed to the country of immigration, education, years of immigration, place of origin, and age.Population of the study was composed of all members of Sudanese community based in the cities of Jeddah and Cardiff. The sample group was composed of 141 families representing 20 % of population of the study – 101 families based in Jeddah; and 40 families based in Cardiff. Members of the sample group have been randomly selected. The researcher uses the analytical descriptive approach.Following are among the most important findings of the study. Parents shall instill patriotism and glorify the homeland among children. As for media, academic and cultural materials should be broadcasted in mass media, by which values of patriotism and national affiliation would be enhanced. As for the official role of the state, it would be embodied in providing expatriates land plots to encourage them to come back to homeland.In view of the findings concluded by the study, the researcher furnished a number of recommendations such as the following. Parents should instill values of patriotism among children. The study also recommended circulation of establishment of Sudanese schools abroad. The role of media should be activated so serve expatriates through broadcasting academic and cultural materials in various mass media. The state would grant land plots to expatriates so as to encourage them to come back home.
Keywords: strategies; national belonging; immigrants